2022
DOI: 10.1016/j.matpr.2020.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and ADMET study of bioactive compounds of Glycyrrhiza glabra against main protease of SARS-CoV2

Abstract: Recent pandemic situation of COVID-19 is caused due to SARS-CoV2 and almost all the countries of the world has been affected by this highly contagious virus. Main protease (M pro ) of this virus is a highly attractive drug target among various other enzymes due to its ability to process poly-protein that is the translated product of the SARS-CoV2 RNA. The aim of the present study demonstrates molecular docking study of Glycyrrhiza glabra (Gg) active compounds such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…Recently in 2020, Nguyen et al [50] also unveiled the fact that Gly143, Cys145, Glu166, and His163 of M pro are the region to form a hydrogen bond and highly favorable molecular fragments for the development of novel SARS-CoV-2 main protease inhibitors, which resembles the finding in the current study. An in silico study performed by Srivastava et al demonstrates the binding stability of Glycyrrhiza glabra derivatives, i.e., GA as bioactive inhibitor inside the SARS-CoV-2 M pro and proposed HIS41, GLY143, GLN189, GLU166, CYS145, THR25, ASN142, MET49, and PRO168 present in the active site of M pro were shown to make non-covalent interaction with the target compound, which was found consistent with our observation [51].…”
Section: Binding Interactions Of Potential Antiviral Agents At the Acsupporting
confidence: 90%
“…Recently in 2020, Nguyen et al [50] also unveiled the fact that Gly143, Cys145, Glu166, and His163 of M pro are the region to form a hydrogen bond and highly favorable molecular fragments for the development of novel SARS-CoV-2 main protease inhibitors, which resembles the finding in the current study. An in silico study performed by Srivastava et al demonstrates the binding stability of Glycyrrhiza glabra derivatives, i.e., GA as bioactive inhibitor inside the SARS-CoV-2 M pro and proposed HIS41, GLY143, GLN189, GLU166, CYS145, THR25, ASN142, MET49, and PRO168 present in the active site of M pro were shown to make non-covalent interaction with the target compound, which was found consistent with our observation [51].…”
Section: Binding Interactions Of Potential Antiviral Agents At the Acsupporting
confidence: 90%
“…Next, we investigated the underlying mechanism of how glycyrrhizin may interfere with the virus replication. Recently, protease inhibitory activity of glycyrrhizin was predicted using in silico simulations [ 8 ]. The SARS-CoV-2 main protease M pro , also known as the 3CL protease, plays a vital role in processing the viral polyproteins that are translated from SARS-CoV-2 RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Glycyrrhizin was discussed in in silico simulations as a potential protease inhibitor [ 8 , 9 ]. Beside the viral main protease (M pro ), the human transmembrane serine protease (TMPRSS2) is another discussed target of glycyrrhizin.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a study demonstrated that GA, Liquiritigenin (L) and Glabridin (G) active compounds of Glycyrrhiza glabra inhibits the enzymatic activity of M pro by binding strongly to the active site. But in comparison to other two compounds GA showed higher binding affinity of -8.0 Kcal/mol [96]. Also, GA could be considered as the best molecule of Glycyrrhiza glabra that could be useful against SARS-CoV-2 [97].…”
Section: Anti-viral Potential Of Glycyrrhiza Glabramentioning
confidence: 87%